Perbandingan Profil Penurunan Muka Air untuk Akuifer Tidak Terkekang Menggunakan 3D Modflow Studi Kasus Pantai Indah Kapuk - Susanto, Amalia; Widjaja, Budijanto; Wijaya, Martin (Universitas Kristen Maranatha, 2025)
Dewatering is required to control the flow of groundwater and to lower the position of the groundwater table during excavation. In planning the dewatering system, parameters related to the flow of water in the soil are required. One of these is the conductivity value, which can be obtained from pumping tests. The sand layer found on the ground surface, which is saturated of water, is referred to as an unconfined aquifer. In this study, conductivity analysis of unconfined aquifer was conducted in PIK2 area using 3 conventional methods which are, Thiem (1906) method and curve matching method of Boulton (1963) and Neuman (1972). Conductivity values obtained from conventional calculations are then analyzed using the help of a program based on the 3D finite difference method Modflow to obtain a pattern of groundwater level decline or can also be called a depression cone. In sandy soil in the PIK2 reclamation area, conductivity values of 5.90×10-5 m/s to 8.08×10-5 m/s were obtained Neuman's method can produce better conductivity values in unconfined aquifers, as shown by the results of the water table profile from the 3D Modflow analysis.